Fluorescent carbon dots in PEC-GS/BG hybrids and their application for bioimaging - Zhang, Xibing; Gong, Jun; Zhou, Hai; Yin, Xun; Wu, Guanda; Wang, Qixiang; Lin, Weipeng; Wang, Huaguo; Ji, Wei; Zhang, Zhongmin (Frontiers in Molecular Biosciences, 2025)
Carbon dots (CDs), renowned for their distinctive photoluminescence properties, have emerged as a prominent material in the field of luminescence. They are extensively utilized in bioimaging, drug delivery, theranostics, and other applications. In this study, CDs were successfully prepared and isolated from PEC-GS/BG hybrids. Their chemical composition, surface functional groups, and crystal structure were comprehensively characterized. The results demonstrated that the CDs are mainly composed of carbon and oxygen. They exhibit a near-spherical morphology with an average diameter of about 7.4 nm. Then, the fluorescent properties of the CDs were thoroughly assessed. Photoluminescence (PL) measurements revealed that the CDs display intense blue fluorescence upon exposure to ultraviolet (UV) light. This emission is excitation-dependent and shows resilience to variations in pH, high ionic strength, and photobleaching. The quantum yield (QY) was determined to be around 4.5%. Additionally, the synthesized CDs exhibited excellent biocompatibility and cell-labeling capability. These findings indicate that the synthesized CDs hold significant potential for practical applications in various fields.